Letter - Holock, C.
C02-0091-001 Telephone SLOANE 7246-9. . . Telegrams: CLERIKOFF PHONE LONDON. GENERAL SECRETARY W.J. BROWN ASSISTANT GENERAL SECRETARY L.C. WHITE FINANCE OFFICE C. HOLOCK ASSISTANT SECRTARIES L.M. SWEET A.B. HALL W.J ELLERBY G.F. GREEN The CIVIL SERVICE CLERICAL ASSOCIATION 2 UPPER BELGRAVE ST. LONDON S.W.1 17th September, 1937. Dear Sir, You will recollect we have been running an Ambulance Appeal amongst our people and to-date we have secured the sum of £450. It was our intention to provide a "C.S.C.A. Ambulance", but we should like to hear from you as to whether this amount is sufficient, It may very well be that an additional few pounds will be subscribed, but it has occurred to me that if we should require say a further £40 or £50 in order to meet our objective it might be a good idea if you sent a letter to me stating that you are pleased to note the result of the effort we have made but pleading for a further sum of X£s in order that the Ambulance might be provided. That letter could be published in our journal together with a further appeal and it might have the effect of producing the goods. If on the other hand you can provide an Ambulance for £450 we shall be pleased if you would go ahead with the manufacture and later on we can make arrangements for the official handing over. Yours sincerely, C. Holock Finance Officer. G. Jeger, Esq., 24, New Oxford Street, W.C.1. 292C/946/2/91